2021
DOI: 10.1101/2021.08.01.454642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary analysis of THAP9 transposase: conserved regions, novel motifs

Abstract: THAP9 is a transposable element-derived gene that encodes the THAP9 protein. It is a homolog of Drosophila P-element transposase (DmTNP). hTHAP9 belongs to the THAP (Thanatos-associated protein) protein family in humans, which has twelve proteins (hTHAP0-hTHAP11). Human THAP proteins have a ~90 amino acid long conserved THAP domain located at the N-terminal end of the protein. The THAP domain is a C2CH type Zinc Finger domain that binds specific DNA sequences and has a conserved secondary structure, namely a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that THAP9 is a highly conserved gene, which has been identified in 178 organisms [ 106 ]. The human THAP9 gene has 6 isoforms, out of which only one is known to encode for aprotein that is homologous to the Drosophila P-element transposase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that THAP9 is a highly conserved gene, which has been identified in 178 organisms [ 106 ]. The human THAP9 gene has 6 isoforms, out of which only one is known to encode for aprotein that is homologous to the Drosophila P-element transposase.…”
Section: Discussionmentioning
confidence: 99%